Vision d'une révision du Code du travail - Verge, Pierre (Les Cahiers de droit, 1979)
Would a codification of labour law — in the Continental meaning of the word, and not a mere consolidation of existing statutes — enhance the development of this field of law ? Would the resulting instrument be likely to generate more appropriate ways of dealing with labour situations, whether or not they pertain to a collective bargaining context ? Adjective as well as substantive law would have to be involved in such an exercise. The latter aspect raises the fundamental issue of the proper relationship between the general law — civil law essentially — and labour law. What degree of autonomy is necessary to the integrity of the specialized law ? Conversely, to what extent is the general law to be relied upon to provide the necessary second-line set of legal provisions ? For instance, the two sets of legal rules entertain different views as to the termination of the employment relationship and as to the effect of a collective agreement. A well-integrated body of labour law should, in the author's opinion, govern comprehensively labour situation. The codifying process would also aim at eliminating internal discrepancies and a simpler, more accessible legal subsystem would emerge. As to the adjective aspects of labour law, the identification of desirable forms of third-party intervention relating to both collective bargaining and labour standards legislation could lead to appropriate jurisdictional arrangements. In the case of industrial conflicts, of particular interest are the flexible powers of intervention with which the Canada and British Columbia labour boards are endowed. Consideration should also be paid to certain European models — namely the Conseil de prud'hommes — which allow both conciliation and adjudication to take place in the solving of normative law conflicts of application. A full-fledged Labour Code would indeed invite the setting up of a more authentic Labour Court.